Strategies to Ameliorate Oxidative Stress During Assisted Reproduction - Agarwal, Ashok; Durairajanayagam, Damayanthi; Virk, Gurpriya; Du Plessis, Stefan S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book discusses the various antioxidants that are in use to overcome oxidative stress in an assisted reproduction setting. Antioxidant therapies may range from enzymatic and non-enzymatic antioxidants, either alone or in combination. While no one antioxidant regime has been identified as effective in improving fertilization and pregnancy rates, antioxidant supplementation has been shown to defend sperm cells from lipid peroxidation and oxidative damage to DNA, and thus improve pregnancy rates. The prevention of oxidative stress and its consequent damage is imperative to ensure a successful outcome of the in vitro fertilization procedure and embryo transfer. Strategies that could be employed to minimize or prevent the detrimental effects of OS during assisted reproduction include supplementation with various types of antioxidants.
Introduction -- Sources of ROS in ART -- Antioxidant Strategies -- Role of Combined Antioxidants -- Conclusion.
Keywords: Reproductive medicine; Embryology; Reproductive Medicine; Embryology